GROWTH RESPONSE OF CUCUMBER UNDER GREENHOUSES COVERED WITH PLASTIC FILMS - A. A. Alsadon; I. M. Al-Helal; A. A. Ibrahim; A. M. Abdel-Ghany; S. M. Al-Zaharani; S. K. H. Gulrez (Journal of Animal and Plant Sciences, 2016)
Greenhouse overheating in summer is a major challenge that greenhouse growers face in arid regions. In comparison with two commercial plastic films, a new NIR-reflective plastic film was tested for effectiveness in reflecting some of the NIR radiation and transmitting most of the PAR into the greenhouse. Three identical greenhouses were built and covered by one of these films. Cucumbers (cv. Sovana F1) were grown in each greenhouse in 30 cm diameter pots with plant density of 2.5 plants m-2. Vegetative, fruit and yield traits were measured at 15 days intervals.  The growth indices were calculated such as leaf area index (LAI), leaf area duration (LAD), leaf weight ratio (LWR), stem weight ratio (SWR), specific leaf area (SLA), leaf area ratio (LAR), unit leaf area (ULR), relative growth rate (RGR), and crop growth rate (CGR). Plants grown under the new plastic film gave the highest values for vegetative, growth indices, fruit and yield traits as compared with the commercial plastic films. In addition, they showed highly significant correlations between growth indices. It can be concluded that growth indices can be used as tools to explain morphological and/or functional plant responses under greenhouse conditions.
Keywords: arid region; greenhouse; plastic cover; growth indices; cucumber; covering materials; solar radiation; PAR; RGR